IGNORING FAMILY LAW ADMINISTRATIVE PROCEDURE: Falsifying Death of Spouses for the Registration of New Marriage in Lengayang Muslim Community - Salma, Salma; Wahida, Hasanatul; Adib bin Samsudin, Muhammad (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
The exercise of the right to register marriage and divorce frequently has to deal with the complexity of the administrative procedure. Consequently, many marriages and divorces are not registered in state institutions which lead to the next difficulty of registering new marriages for those who unregistered their divorce previously. However, a different fact happens in Lengayang, where local and state authorities collaborated to tackle administrative constraints. This paper sheds light on the shortcut taken by the Lengayang people who falsified the death of their spouses to legally register their new marriages. Data was collected through interviews and document analysis. It is then analyzed qualitatively. This article reveals that the falsification of death was utilized by Lengayang people to wittingly subdue the legal administration. This practice was backed up by the local authorities, such as ninik mamak as a customary institution, wali jorong or wali nagari as the head of the villages. The economy (the high cost), the geography (the distance of the religious court from people's domiciles), and the deadlock of social relationships between spouses foster this falsification.[Pelaksanaan pendaftaran perkawinan dan perceraian seringkali harus berhadapan dengan kompleksitas administrasi. Akibatnya, banyak perkawinan dan perceraian yang tidak dicatatkan di lembaga negara yang mengakibatkan sulitnya pencatatan perkawinan baru bagi mereka yang tidak mendaftarkan perceraiannya sebelumnya. Namun tidak bagi masyarakat Lengayang, di mana otoritas adat (lokal) dan otoritas negara bekerja sama untuk mengatasi kendala administratif tersebut. Tulisan ini menyoroti tindakan administrasi yang dilakukan oleh masyarakat Lengayang yang memalsukan kematian mantan pasangannya untuk mendaftarkan pernikahan barunya secara resmi. Pengumpulan data dilakukan melalui wawancara dan analisis dokumen. Data kemudian dianalisis secara kualitatif. Artikel ini mengungkapkan bahwa pemalsuan kematian dimanfaatkan oleh sebagian masyarakat di Lengayang untuk (secara sadar) menerobos hambatan administrasi hukum perkawinan. Praktik ini didukung oleh penguasa setempat, seperti ninik mamak sebagai kepala suku dan wali jorong atau wali nagari sebagai kepala desa. Mahalnya biaya, jauhnya jarak geografis ke Pengadilan Agama, dan mandeknya relasi (komunikasi) antara suami istri mendorong praktik pemalsuan kematian ini.